Historicizing Kwaito - Steingo, Gavin (International Library of African Music, 2008)
In the standard narrative, kwaito is described as a form of electronic dance music that emerged alongside the democratization of South Africa between Nelson Mandela's release from prison (1990) and the democratic elections of 1994. In most cases, scholars have claimed that kwaito emerged as a direct response to the end of apartheid and the birth of the South African "rainbow nation”. While there is certainly some truth in such a claim, the present essay is an attempt to complicate this rather simplistic and monolithic historical narrative.
Keywords: African Music